Emerging Patterns in Antimicrobial Susceptibility Profiles of Pseudomonas SPP- Hospital Based Study - Sadia Ikram, Saima Inam, Saba Shamim, Syed Zeeshan Haider, Muhammad Atif Qureshi, Asma Inam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There is an emerging trend of pseudomonas infections in immune-compromised patients, specifically in hospital settings. The flagship member of this family is Pseudomonas aeruginosa, which is a major infectious agent. This study assessed the distribution and susceptibility patterns of Pseudomonas species isolated from various specimens as a part of surveillance program, in order to devise antibiograms. Aim: To determine frequency & antimicrobial sensitivities of Pseudomonas species in a tertiary care hospital from Lahore. Study design: Retrospective, descriptive, cross sectional study Place & duration of study: Conducted in a tertiary care hospital in Lahore, from January 2021 to January 2022. Methods: Thirty two isolates of Pseudomonas species from different clinical specimens were isolated in microbiology section of a tertiary care hospital during a period of 13 months. MacConkey and blood agar were utilized for culturing of organisms. Gram staining, oxidase, and catalase testwere utilized for phenotypic characterization. Antibiotic susceptibility testing against anti-pseudomonal drugs was performed according to the Clinical and Laboratory Standards Institute guidelines (CLSI) 2021. Results: The inference drawn at the end of study was that, out of thirty two isolates of Pseudomonas species received and pus was the most common specimen (46.8%), followed by 18.75% from urine specimens. 62.5% of the pseudomonas species were obtained from male patients. The most affected age group was 40-60 years, followed by 1-20 years. The most sensitive options turned out to be Imipenem (65.6%) and Pipericillintazobactam (62.5%), followed by 59.3% sensitivity in Amikacin. The least sensitive options in the study isolates were Aztreonam (15.6%) and Ticarcillin clavulanic acid (25%). In 18% of pseudomonas species isolated from urine cultures, fosfomycin was 83.3%, whereas nitrofurantoin turned out to be 50% sensitive. Conclusions: The steadily rising resistance in Pseudomonas species againstavailable antibiotics optionsnecessitates their use inlife-threatening and hospital acquiredinfections. Keywords: Peudomonas, Flouroquinolones, Carbapenem